Kombinasi Metode Aras Dan Roc Dalam Sistem Pendukung Keputusan Pemilihan Kepala Lab Teknik Komputer Dan Jaringan - Ridho Adrian; Guidio Leonarde Ginting; Kurnia Ulfa (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The head of the computer laboratory is the person who leads and coordinates all planning, implementation and control activities in the laboratory and receives all periodic reports from laboratory staff and evaluates all existing activities and reports the results of the evaluation to the leadership. However, in the selection process, there were so many enthusiasts and the selection stages were so long, such as administration selection, competencies and interviews, that it was difficult for the school to make a decision in getting a new laboratory head candidate as expected. To overcome the problem of choosing a laboratory head who is difficult to make decisions, a decision support system is needed. A decision support system is a system capable of solving a problem and facilitating decision making. The method used for decision making is by using a combination of Additive Ratio Assessment (ARAS) and Rank Order Centroid (ROC) methods. This method is used to carry out settlements where the ROC method is used to find weight values and the ARAS method is used for a ranking based on existing criteria such as expertise, level of education, age, length of teaching and discipline. Where each criterion has its own weight value and the alternatives will be ranked. After doing a ranking, the results obtained from the combination of the ARAS method and the ROC method are M. Agus Salim Siregar (A4) with a score of 3.2794. These results can facilitate the selection team in making decisions and being elected as the head of the computer and network engineering laboratory at the Musda Perbaungan Private Vocational School.